2013
DOI: 10.1007/s10103-013-1264-y
|View full text |Cite
|
Sign up to set email alerts
|

Liver regeneration following partial hepatectomy is improved by enhancing the HGF/Met axis and Akt and Erk pathways after low-power laser irradiation in rats

Abstract: A simple, easy, and safe procedure aiming to improve liver regeneration could be of great clinical benefit in critical situations such as major hepatectomy, trauma, or hemorrhage. Low-power laser irradiation (LPLI) has come into a wide range of use in clinical practice by inducing regeneration in healthy and injured tissues. However, the effect of LPLI on the process of liver regeneration, especially those related to the molecular mechanisms, is not fully understood. Thus, the aim of the present study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 43 publications
1
28
1
1
Order By: Relevance
“…Araújo and co-workers observed that, after 632.8 nm PBM, hepatectomized animals showed an increase in the expression of HGF followed by increased phosphorylation of Met and its downstream signaling molecules Akt and ERK. This indicates that PBM could enhance liver regeneration after hepatectomy [97]. …”
Section: Molecular Mechanisms Of Pbmmentioning
confidence: 99%
“…Araújo and co-workers observed that, after 632.8 nm PBM, hepatectomized animals showed an increase in the expression of HGF followed by increased phosphorylation of Met and its downstream signaling molecules Akt and ERK. This indicates that PBM could enhance liver regeneration after hepatectomy [97]. …”
Section: Molecular Mechanisms Of Pbmmentioning
confidence: 99%
“…Low-power laser irradiation (LPLI) is suggested to be an effective minimally invasive palliative treatment option for patients with small liver tumors [119,120] . Interestingly in this context was that LPLI was shown to improve liver regenerative capacity of a small liver remnant after hepatectomy through activation of the HGF-MAPK/PI3K pathway [121] .…”
Section: Trendsmentioning
confidence: 99%
“…As demonstrated, lack of FGF15/19 resulted in decreased FGFR4 and cyclin A in non-steatotic livers undergoing CD and I/R injury associated with LT. The important role for ERK1/2 in LT and experimental models of liver regeneration in non-steatotic livers has been previously demonstrated [45,[68][69][70][71][72][73]. Thus, it could be bearing in mind the possibility that failure in cell proliferation induced by FGF15 inhibition could be related to a reduced activation of ERK1/2.…”
Section: Discussionmentioning
confidence: 92%